Effects of cooling rates on the quality of Prochilodus lineatus (Valenciennes, 1836) sperm. Issue 7 (27th May 2019) - de Jesus Paula, Daniella Aparecida; Murgas, Luis David Solis; Castro, Tássia Flávia Dias; de Lima Assis, Isadora; Neto, Rafael Vilhena Reis; Marcussi, Silvana
Abstract: This study aims to investigate the effect of different cooling rates on the semen cryopreservation of curimba ( Prochilodus lineatus ). Nineteen ejaculates were obtained from adults males and cryopreserved at 15°C/min (CR15), 30°C/min (CR30) (controlled temperature inside and outside straw, speed was stable during freezing) and direct freezing in liquid nitrogen vapour (~35.6°C/min) (CRNV). The straws were thawed and seminal parameters evaluated. DNA fragmentation through the comet assay was assessed. A fresh sperm sample was not frozen and used for analyses. Data were submitted to an analysis of variance (ANOVA), and means were compared by Scott–Knott test ( p  < 0.05) using the R Software. Mean motility percentage was 100%, and motility duration was 39.5 ± 5.7 s for the fresh sperm (subjective analysis); 58.9 ± 8.0% and 24.5 ± 5.7 s for CR15; 64.8 ± 4.8% and 26.5 ± 7.1 s for CR30; and 50.1 ± 16% and 25.7 ± 4.7 s for CRNV, respectively. Motility percentages were higher and equal between CR15 and CR30 compared to CRNV ( p  < 0.05). Some sperm motion kinetics, namely average path velocity (VAP) and straight line velocity (VAS), were higher for CR30 ( p  < 0.05), while curvilinear velocity (VCL) and velocity progression (PRO) were lower for CRNV ( p  < 0.05). Straightness (STR) and wobble (WOB) were the same among treatments ( p  > 0.05). Sperm morphology results indicated higher means for total morphological sperm alterations in CRNV. All cooling rates caused sperm DNA fragmentation, although CR30 provided a less harmful effect. This is the first report for cryopreserved P. lineatus sperm preserved under different controlled cooling rates. The cooling rate of 30°C/min is indicated for the cryopreservation of this fish sperm as it led to the lowest detrimental spermatozoa effects.